British politics - Leach, Robert 1941- (Palgrave Macmillan Ltd, 2011)
Systematically revised and updated, British Politics is an accessible and definitive guide to the shape of Britain's political institutions and processes. The new edition covers significant developments and events in British politics, such as the financial crisis and the 2010 general election, and provides full analysis of the first year of the Conservative-Liberal Democrat coalition government. Incorporating useful learning aids throughout, the book examines the state of British politics set against the background of devolution within the UK and an ever-changing European and global en
Keywords: Politisches System; Großbritannien; Lehrbuch